The shepherd's life : modern dispatches from an ancient landscape - Rebanks, James (Flatiron Books, 2015)
Some people's lives are entirely their own creations. James Rebanks' isn't. The first son of a shepherd, who was the first son of a shepherd himself, his family have lived and worked in the Lake District of Northern England for generations, further back than recorded history. It's a part of the world known mainly for its romantic descriptions by Wordsworth and the much loved illustrated children's books of Beatrix Potter. But James' world is quite different. His way of life is ordered by the seasons and the work they demand. It hasn't changed for hundreds of years: sending the sheep to the fells in the summer and making the hay; the autumn fairs where the flocks are replenished; the grueling toil of winter when the sheep must be kept alive, and the light-headedness that comes with spring, as the lambs are born and the sheep get ready to return to the hills and valleys.